Evaporation-Induced Water and Solute Coupled Transport in Saline Loess Columns in Closed and Open Systems - Jian Xu; Wei Lan; Yanfeng Li; Wen-Chieh Cheng; Jun Yuan; Qinghai Tan (Geofluids)
Evaporation-induced water and solute coupled transport is a significant cause for soil salinization that leads to a series of engineering and environmental problems. In the artificial evaporation environment, including relative humidity, atmospheric temperature, atmospheric pressure, radiation intensity, and wind speed, evaporation of loess columns with sodium sulfate, temperature profile, and water and solute transport in closed and open systems were investigated. In the former case, a range of stability was noted in the lower part of the column where the heat, water, and solute coupled transport only exhibited a weak response to a specified evaporation environment. As the environment was more favorable for evaporation, or at a higher gradient of temperature, this range extended downwards, while above this range the heat, water, and salt profiles in the evaporation-affected domain changed dramatically, characterized by a basic law that solutes moved with water and were then retained with water desalinated. Evidences were found from the profiles that the water contents in the evaporation-affected range decreased but the salt contents increased, especially in the surface. In an open system, by contrast, there was little difference in temperature but greater in water and salt profiles. Three stages were found from the supply of external water during evaporation. In the initial stage, the higher gradient formed between the initial moisture state and the preset external water level led to a rapid supply of external water. As the evaporation proceeded, a relatively stable water profile was reached as the intensity of water supply approached to that of evaporation, accompanied by a continual migration of solutes towards the surface. Due to the accumulation of precipitated salts, water transport was slowed down, and the intensity of water supply decreased. The changes in soil suction may account for the above behavior.